HUBUNGAN POLA MAKAN DAN AKTIVITAS FISIK TERHADAP KADAR KOLESTROL PADA APARATUR SIPIL NEGARA - Syarfaini, Syarfaini; Ibrahim, Irviani Anwar; Yunliana, Yuliana (Jurnal Kesehatan, 2020)
High level of cholesterol in blood circulation has become a serious problem because it can cause various health problems including non-communicable diseases such as heart diseases, stroke, and mellitus. This research investigates the correlation between the eating patterns and physical activity with their cholesterol level of the civil servants at Local Education Authority of Makassar. It uses quantitative method, cross sectional study research approach, and analytical survey as the research design to examine the issue. The samples consist of 36 civil servants who are selected using purposive sampling technique from a population of 103 civil servants of the Local Education Authority of Makassar. The research data consist of primary and secondary sources. The data about samples’ cholesterol status are obtained through cholesterol level test by utilising Easy Touch and FFQ forms as well as physical activity Recall. Drawing on the results of cross tabulation analysis of chi square test, this research concludes that there is a significant correlation between the eating patterns and the cholesterol level of the civil servants of the Local Education Authority of Makassar (p =0.030). However, the results of analysis show no significant correlation between the physical activity and the cholesterol level of the civil servants of the Local Education Authority of Makassar (p =0.830). This, this research recommends that the civil servants with high cholesterol level to do treatments for reducing their cholesterol level.